Ball & beam control system using matlab and lego nxt - Mariño Lizarazo, Daniel Leonardo; Tumialan Borja, Jose Antonio (Visión electrónica, 2014)
The LEGO Mindstorms NXT, are being used today in graduate and undergraduate courses especially on issues related to robotics and control, but in other engineering issues, such as data acquisition and signal filtering can be easily used to strengthen the understanding of those concepts in the labs . These practices require physical educational tools should be inexpensive, easy to use and multi -purpose application form that encourages student learning. In the present study we use only LEGO Mindstorms NXT (Ball & Beam) as a training platform, but not imitating the same commercial kits approach because it presents a typical problem of ball and beam control. The prototype was built and instrumented with sensors and actuators LEGO standard for subsequent modeling, identification and simulation using the Matlab R software. Three controllers were designed, the first is a cascade control and the other two are state space observer’s control (feedback: proportional and integral). Once simulated controllers are implemented in software using BricxCC prototype, where the results were satisfactory, showing the balance of the ball to the three controllers, each different features presented in steady state and a settling time that varies between 1.5 and 3 seconds